2009
DOI: 10.1039/b901248f
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence vapochromic properties of a platinum(ii) complex with 5,5′-bis(trimethylsilylethynyl)-2,2′-bipyridine

Abstract: A platinum(II) complex of 5,5'-bis(trimethylsilylethynyl)-2,2'-bipyridine displays unusually reversible colour and luminescence changes when exposed to specific organic vapours, correlated well with Pt...Pt distances as well as pi-pi and C-H...(C[triple bond]C) interactions in the stacking of square-planar platinum(II) moieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 32 publications
(27 reference statements)
0
57
0
Order By: Relevance
“…Chen and co‐workers also reported an interesting vapochromic Pt II complex, [Pt(Me 3 SiC≡CbpyC≡CSiMe 3 )(C≡Cbpy) 2 ] ( 12 ; Figure 15, left) composed of two kinds of rigid ligands [Me 3 SiC≡CbpyC≡CSiMe 3 = 5,5‐bis(trimethylsilylethynyl)‐2,2′‐bipyridine, HC≡Cbpy = 5‐ethynyl‐2,2′‐bipyridine] 43. X‐ray crystallographic analysis for the chloroform and water co‐adsorbed form 12· 1.5CHCl 3 · 0.5H 2 O indicated that the Pt ··· Pt metallophilic interaction was effective within the dimer [Pt ··· Pt distance = 3.2363(15) Å; Figure 16, left], whereas the Pt ··· Pt distance beyond 4.0 Å in the antiparallel‐packed dimer suggested negligibly weak metallophilic interaction between the Pt II ions in the dichloromethane‐solvated form 12· CH 2 Cl 2 (Figure 16, right).…”
Section: Hydrophobic–hydrophobic Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen and co‐workers also reported an interesting vapochromic Pt II complex, [Pt(Me 3 SiC≡CbpyC≡CSiMe 3 )(C≡Cbpy) 2 ] ( 12 ; Figure 15, left) composed of two kinds of rigid ligands [Me 3 SiC≡CbpyC≡CSiMe 3 = 5,5‐bis(trimethylsilylethynyl)‐2,2′‐bipyridine, HC≡Cbpy = 5‐ethynyl‐2,2′‐bipyridine] 43. X‐ray crystallographic analysis for the chloroform and water co‐adsorbed form 12· 1.5CHCl 3 · 0.5H 2 O indicated that the Pt ··· Pt metallophilic interaction was effective within the dimer [Pt ··· Pt distance = 3.2363(15) Å; Figure 16, left], whereas the Pt ··· Pt distance beyond 4.0 Å in the antiparallel‐packed dimer suggested negligibly weak metallophilic interaction between the Pt II ions in the dichloromethane‐solvated form 12· CH 2 Cl 2 (Figure 16, right).…”
Section: Hydrophobic–hydrophobic Interactionsmentioning
confidence: 99%
“… Structural representation of 12 (left) and emission spectra of solid‐state 12· guest (right). Reprinted with permission from the literature 43. Copyright 2009 The Royal Society of Chemistry.…”
Section: Hydrophobic–hydrophobic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vapo‐ and mechanoluminescent complexes in the solid state show reversible emission‐color changes in the visible or near‐infrared regions. These spectral shifts, as responses of VOCs or mechanical force, generally originate from molecular conformation changes in the solid state, e.g., metal–metal distance,322, 40, 41, 4345 coordination of VOCs,2326 trapped VOCs in a crystal lattice,2729 weak noncovalent interactions (π–π interaction, hydrogen bonding, CH–π interactions),8, 11, 19, 20, 26, 30–36, 40, 43, 47 isomerization involving polymer complexes and oligomers,37 and planarization of the conjugated ligand 46. Up to now, a number of linearly‐coordinated Au I systems have been reported as vapoluminescent compounds3, 6, 9 or mechanoluminescent materials 3941.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] As a continuation this work, herein an exact example of how the packing structure and photophysical properties of a platinum(II) chloride complex, Pt(4,4Ј-dibromo-2,2Ј-bipyridine)Cl 2 (1), are affected by different amount of CH 2 Cl 2 crystalline solvate molecules is described.…”
Section: Introductionmentioning
confidence: 99%